PENGARUH DIGITAL PAYMENT TERHADAP PENINGKATAN VOLUME PENJUALAN UMKM DI TELUKJAMBE TIMUR - Natalya Puspawangi Nurhanifah; Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the use of digital payment, Micro, Small, and Medium Enterprises (MSMEs) in the area can enhance efficiency, security, and convenience in financial transactions. Local government has implemented policies and regulations to support Micro, Small, and Medium Enterprises (MSMEs) in utilizing digital payment technology, including fiscal incentives and training. Previous studies indicate that MSMEs using digital payment tend to experience revenue and sales growth. The research aims to determine the extent of MSMEs using digital payment, whether digital payment can boost sales volume and profitability of MSMEs, and how MSMEs perceive the ease of use, security, and benefits of digital payment. The findings are expected to provide a better understanding of the impact of digital payment on the growth of MSMEs in Telukjambe Timur.